2020
DOI: 10.1515/ntrev-2020-0065
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized layered double hydroxide applied to heavy metal ions absorption: A review

Abstract: The use of functional material can help mitigate the pollution by heavy metals, which presents an array of risks to human production and life. This work provides a comprehensive review of the current knowledge on functionalized layered double hydroxide (LDH) as a heavy metal absorption material, by synthesizing the information from a total of 141 relevant publications published since 2005. LDH provides a potentially highly efficient method to adsorb heavy metal ions, which is simple to prepare and of low cost.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 137 publications
1
28
0
Order By: Relevance
“…In addition, the oxygen adsorbed on the surface of MB can accept electrons and form superoxide radical anions (O 2 ), which also results in the formation of OH upon protonation. These OH and O 2 are responsible for the decomposition of MB under light irradiation ( Zhang et al, 2010 ; Liu et al, 2013 ; Tang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the oxygen adsorbed on the surface of MB can accept electrons and form superoxide radical anions (O 2 ), which also results in the formation of OH upon protonation. These OH and O 2 are responsible for the decomposition of MB under light irradiation ( Zhang et al, 2010 ; Liu et al, 2013 ; Tang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption capacity of NiAl-LDH, Biochar and graphite has decreased signi cantly in the regeneration process, this is because the material has an unstable structure which results in exfoliation when used repeatedly (Palapa et al, 2020d) and structural damage. So it can be concluded that LDH modi cation with carbon-based materials can improve the stability of the LDH structure (Tang et al, 2020) . Thermodynamic parameters were studied through variations in the initial concentration of Fe(II) ions and the adsorption temperature as shown in Figure 7.…”
Section: Adsorptionmentioning
confidence: 99%
“…LDHs are very versatile for different technological applications, in particular biological and chemical ones [21], primarily due to their layered structure, which allows for hosting even complex organic molecules, such as drugs and biomolecules, that are intercalated in the large interlayer space with wide flexibility regarding the composition and functionalization [22][23][24][25][26][27][28]. Moreover, there is currently an increasing interest in LDHs due to their properties as heterogeneous catalysts and supports for molecular catalysts [29][30][31] or photocatalysis [32], for fabrication of superhydrophobic surfaces [33,34], water treatment and remediation [35][36][37] and ion-exchanger membranes [38,39]. Interestingly, anion conductivity in LDHs can be modulated by incorporating different anions in the interlayer space, allowing for their use as sensors [40][41][42][43][44] or as fillers in different electrochemical applications, such as fuel cells, supercapacitors and water splitting [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is currently an increasing interest in LDHs due to their properties as heterogeneous catalysts and supports for molecular catalysts [29][30][31] or photocatalysis [32], for fabrication of superhydrophobic surfaces [33,34], water treatment and remediation [35][36][37] and ion-exchanger membranes [38,39]. Interestingly, anion conductivity in LDHs can be modulated by incorporating different anions in the interlayer space, allowing for their use as sensors [40][41][42][43][44] or as fillers in different electrochemical applications, such as fuel cells, supercapacitors and water splitting [45][46][47].…”
Section: Introductionmentioning
confidence: 99%